PENENTUAN ZONA PROSPEK HIDROKARBON PADA FRACTURED BASEMENT BERDASARKAN DATA WELL LOG DAN SEISMIK 3D PADA LAPANGAN MALAWAPATI SUB-CEKUNGAN JAMBI, CEKUNGAN SUMATERA SELATAN - Rahman Wahyudianto; Hadi Nugroho; Yoga Aribowo; Robet Wahyu Widodo (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Hydrocarbon discovery in the basement of several exploration wells in South Sumatra Basin, giving new challenges for geologists to find hydrocarbon reserves with the concept of new thinking, the best one on the concept of the geology and oil exploration in fractured basement.Research object is on the basement high, which dominant lithology is schist. This research is located at Malawapati and includes part of the Sub-Basin of Jambi, South Sumatra Basin. Based on Drill Stem Test (DST), hydrocarbon potential of fractured basement on Prabu X1 is around 0.2-1 MMSCFGPD (Million Standard Cubic Feet Gas Per Day) and on Dharma X3 is around traces-1 MMSCFGPD, then it needs a good study to determine hydrocarbon potential in the fractured basement.The purpose of this research is obtaining a description of the basement characteristic and vertical fracture intensity in the basement by using well log and master log, obtaining horizontal fracture distribution in the basement by using 3D seismic and seismic attributes, obtaining a description of the basement geometry by analyzing geological structures in the basement, determining correlation of the two data are intensity and distribution of fracture to determine the location of the most prospect as a hydrocarbon zone.The research method is using descriptive and analytical methods. There are 3 wells in Malawapati field. There are 2 wells which reaching the basement, which are Prabu X1 and Dharma X3 and also a well not reaching the basement, which is Dharma X3. Well log and master log is used to determine basement characteristics and vertical fracture intensity with Fuzzy Inference System (FIS), it is used for reference in retraction the target zone on seismic attribute by type variance cube, which the suitable are 70 ms below the horizon of Prabu X1 and 25 ms below the horizon of the well Dharma X3. 3D seismic data is used to determine basement geometry and horizontal fracture distribution with seismic attribute by type variance cube.Based on the correlation analysis of well log, master log and seismic attribute by type variance cube, is known that hydrocarbon prospect zone in vertical is weathered basement zone and high intensity zone. Hydrocarbon prospect zone in horizontal is zone A which is the top of basement high zone and also not affected by zone fault so it has low fracture intensity. Zone B is edge of the basement high zone and also affected by zone fault so it has high fracture intensity